Identification and analysis of the gene cluster involved in biosynthesis of paenibactin, a catecholate siderophore produced by Paenibacillus elgii B69 - Yanping Wen; Xuechang Wu; Yi Teng; Chaodong Qian; Zhajun Zhan; Yuhua Zhao; Ou Li (Environmental Microbiology, 2011)
Summary Bacteria belonging to the genus Paenibacillus are recognized as rich sources of bioactive natural products. To date, there are few characterized siderophores from this genus. Here, through genome analysis, we identified a non‐ribosomal peptide biosynthetic gene cluster ( pae ) responsible for siderophore assembly in Paenibacillus elgii B69. The 12.8 kb gene cluster comprises six open reading frames encoding proteins similar to the components of the bacillibactin biosynthetic machinery and bacillibactin esterase. To examine the product of the pae gene cluster, we cultured P. elgii B69 in iron‐deficient medium for siderophore expression. A novel siderophore structurally similar to bacillibactin, designated paenibactin, was purified and characterized. Its structure was determined as a cyclic trimeric lactone of 2,3‐dihydroxybenzoyl‐alanine‐threonine. The involvement of the pae gene cluster in paenibactin biosynthesis was confirmed by the biochemical assay of adenylation domain specificity. Furthermore, we demonstrated that the pae gene cluster evolves from an ancestral bacillibactin biosynthetic gene cluster via sequence and phylogenetic analyses. The structural difference between paenibactin and bacillibactin may stem from a mutation‐induced change in the adenylation domain specificity. Based on these findings and published models for bacillibactin, we proposed models for paenibactin biosynthesis, ferric–paenibactin uptake and paenibactin‐bounded iron release.